Destino da ilha sob a mira do Éden : Fernando de Noronha no percurso do tempo. - Dantas, Pedrianne Barbosa de Souza (2009)
The archipelago of Fernando de Noronha was listed by UNESCO as a mankind patrimony in 2001. Nowadays it is a famous touristic destination for travellers from all over the world in searching for wild landscapes. However, Fernando de Noronha has a long history. It was occupied by Europeans since the 16th century and, in these first moments, described as a sort of paradise. Since that, it has been cumulated different memories. In the 17th century, it was invaded by the Dutch that used the main island as an acclimation garden. In the 18th century it was occupied by the Portuguese. This is the time of the foundation of its most important urban settlement, the Vila dos Remˆdios, surrounded by fortifications. It was kept as a prison until the 20th century. Only in the last decades, it started to be, again, admired for its nature. Remains of the fortresses and a significant part of the old Vila dos Remˆdios reached the present days. However, listed for its natural beauty, the architectonical and urban patrimony of the archipelago has been kept in silence. This dissertation intends on the comprehension of the interference of the edenic mytography in the process of the exploration of America, in a way that the sailors, missionaries, colonists and in the present time the tourists, they did and they ve been doing the recognition of a landscape which has glimpsed from many medieval descriptions that attended the scenario of the Garden of Eden in a hopeful search for the lost paradise after the sin and the expulsion of Adam and Eve and the difficulties and the requirements to have access to it.